2014
DOI: 10.3892/mmr.2014.2163
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of sorafenib on the A549/DDP human lung adenocarcinoma cell line in vitro

Abstract: The aim of the present study was to observe the effects of sorafenib on the proliferation, apoptosis and invasion of A549/DDP cisplatin-resistant lung adenocarcinoma cells cultured in vitro. The A549/DDP cisplatin-resistant lung adenocarcinoma cell strain was cultured in vitro, the cell culture group incubated in culture medium only was set as the control group (Group S0) and the four concentration gradients of sorafenib were added to the culture groups as the experimental groups: S1, 2 µmol/l; S2, 4 µmol/l; S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Sorafenib (NEXAVAR; SOR) is a multi-target protein kinase inhibitor approved for the treatment of hepatocellular carcinoma and advanced renal cell carcinoma [ 39 , 40 ]. Although SOR has not been approved for lung cancer, it is still the subject of extensive research related to lung cancer [ 41 , 42 , 43 ]. Results of the retrospective analysis reported that SOR significantly prolongs the recurrence-free survival of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sorafenib (NEXAVAR; SOR) is a multi-target protein kinase inhibitor approved for the treatment of hepatocellular carcinoma and advanced renal cell carcinoma [ 39 , 40 ]. Although SOR has not been approved for lung cancer, it is still the subject of extensive research related to lung cancer [ 41 , 42 , 43 ]. Results of the retrospective analysis reported that SOR significantly prolongs the recurrence-free survival of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…It also demonstrated that SOR in combination with antitumor mesenchymal stem cells potently inhibited tumor growth and preserved the antitumor-associated anti-inflammatory effects of mesenchymal stem cells [ 46 ]. Although previous studies suggested the efficacy of SOR against lung cancer [ 41 , 43 ] to the best of our knowledge, there is no study evaluating the relationship between JNK and COX-2 signaling and SOX-2 in the lung premalignant microenvironment. Therefore, we aimed to determine the mechanistic effect of SOR in DEN-induced lung carcinogenesis using a rat model.…”
Section: Introductionmentioning
confidence: 99%